Diversity in socioecological niches in the Andes (DISENIA): An isotope-based project - Barberena, Ramiro (2023)
This new project is studying the diversity of socioecological niches across the agropastoral transition in the Andes, utilising a multi-isotope approach to track human territories and allocate subsistence tasks. During the agropastoral period, we discriminate different diachronic niches with varying extents of maize farming and altitudinal mobility.